2019
DOI: 10.1002/ima.22320
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nicergoline treatment on regional cerebral blood flow in early Alzheimer's disease

Abstract: Alzheimer's disease (AD) is associated with reduction of regional cerebral blood flow (rCBF) in various brain regions. Although nicergoline has been used to treat cognitive impairment in various types of dementia, the effect of nicergoline on brain perfusion in AD has not been elucidated. The aim of the study was to examine the effect of nicergoline on rCBF in patients with early AD using technetium‐99m hexamethylpropylene amine oxime single‐photon emission computed tomography (SPECT). For 1.7 years on average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Clinical trials of PF-04447943 and BI 409,306 have shown a lack of efficacy [341,342], which might be because PDE9 inhibition increases periplasma membrane cGMP (rather than cytoplasmic cGMP) and allows Ca 2+ influx through CNG [68,71,213]. The clinical trials of vinpocetine [253,[255][256][257][258], cilostazol [69,[317][318][319], and nicergoline are preliminary and mixed [273][274][275][276][277], with cilostazol and nicergoline likely being the most promising and the worthiest of further study of these three [273][274][275][276][277]. Deprenyl/selegiline clinical trials show short-term but not long-term benefits, making deprenyl somewhat disappointing [289].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Clinical trials of PF-04447943 and BI 409,306 have shown a lack of efficacy [341,342], which might be because PDE9 inhibition increases periplasma membrane cGMP (rather than cytoplasmic cGMP) and allows Ca 2+ influx through CNG [68,71,213]. The clinical trials of vinpocetine [253,[255][256][257][258], cilostazol [69,[317][318][319], and nicergoline are preliminary and mixed [273][274][275][276][277], with cilostazol and nicergoline likely being the most promising and the worthiest of further study of these three [273][274][275][276][277]. Deprenyl/selegiline clinical trials show short-term but not long-term benefits, making deprenyl somewhat disappointing [289].…”
Section: Resultsmentioning
confidence: 99%
“…No statistically significant differences were noted in the severity of dementia, activities of daily living, cognition, and depressive symptoms between baseline and follow-up. However, nicergoline increased cerebral blood flow in frontal and parietal regions [276].A 2019 study in 22 patients with early AD found that, compared to acetylcholine esterase inhibitors alone, acetylcholine esterase inhibitors plus nicergoline preserved cerebral blood flow to the left temporal pole and the middle cingulate gyrus but did not result in any significant difference in dementia severity [277].…”
Section: Nicergolinementioning
confidence: 99%
See 2 more Smart Citations
“…Quantitative CBF serves as a valuable metric for monitoring pathophysiological changes in cerebrovascular function and brain metabolism. Moreover, numerous conditions are associated with alterations in CBF, including cognitive decline, 1 white matter hyperintensity, 2 and Alzheimer's disease 3 . To gain a better understanding of potential changes in brain perfusion across various conditions, it is essential to establish normal reference values and acknowledge intersubject variations.…”
Section: Introductionmentioning
confidence: 99%